Unravelling the User Perception: Evaluating Kenadsa's Heritage Office Building Performance Through Perceptual Dimensions and Behaviors - Hamlili, Fatima Zohra; Dakhia, Azzedine; Biara, Ratiba Widad (Future Science, 2024)
This study investigates the complex relationship between user perceptions and subsequent behaviors in the multisensory environment within Kenadsa’s heritage office building, located in the oasis of Bechar, Algeria. Using a combination of quantitative and qualitative subjective data collection methods, the research aims to assess the perceptual dimensions of the office building's interior space, thermal conditions and lighting environment, as well as to evaluate its performance based on users' perceptions and behaviors. The methodology includes in situ questionnaire surveys conducted after each user's work experience, complemented by thermal and visual assessments observation of the lighting during the winter and summer seasons. The results highlight the dynamic interplay between user perception and behavior, and provide valuable information for improving the design and functionality of heritage buildings in similar contexts.